Marketing pessoal na gestão de carreira: a percepção dos concluintes do curso de Administração da UFAM – campus Parintins - Oliveira, Isabella Rodrigues (Brasil, 2025)
The aim of this work is to identify the perception of graduating students in the administration course regarding the importance of personal marketing and career management. Recently, the job market has become increasingly competitive, which has initiated the demand for a new professional profile, making it essential to stay updated, prepared, and consistently wellinformed to promote personal and professional advancement. In this context, this research was developed with the graduating students of the Administration course at ICSEZ/UFAM, aiming to show how these future professionals perceive the importance of and how they are working on Personal Marketing and Career Management to enter the job market. This research is qualitative in nature, addressing the main themes related to personal marketing and career management, with descriptive objectives and field study technical procedures. Questionnaires were applied to collect data, followed by analysis and interpretation to achieve the expected objectives. The results reveal a significant understanding of the importance of personal branding, career management, and networking. Graduates recognize that "image selling" and "professional posture" are essential for building a personal brand. While they feel confident in their self-awareness, many still seek clarity regarding their professional identity. The interrelationship between networking and career management is valued, highlighting the importance of connections. The responsibility for managing their careers indicates a proactive mindset. Strengthening academic training with practical content on these topics can prepare students for the job market.